BIOM-02. LEPTOMENINGEAL DISEASE SECONDARY TO MELANOMA: UPDATES ON THE VALIDITY OF THE VERIDEX CELLSEARCH SYSTEM. (12th November 2021) - Pina, yolanda; Mokhtari, Sepideh; Kim, Youngchul; Evernden, Brittany; Tran, Nam; Smalley, Inna; Khushalani, Nikhil; Law, Vincent; Puskas, John; Caseres, Gisela; Vogelbaum, Michael; Smalley, Keiran; et al.
Abstract: BACKGROUND: Leptomeningeal disease (LMD) is devastating with a median survival of 8-10 weeks without treatment. LMD affects approximately 5% to 25% of melanoma patients. Its pathophysiology remains unknown and effective treatments are virtually non-existent. The primary aim of this study was to evaluate the validity of Veridex CellSearch® System (VCS) compared to Gold Standard test (i.e., CSF cytology). MATERIALS AND METHODS: A retrospective chart review was performed of subjects with suspected LMD from melanoma enrolled in the MCC 19332/19648 at Moffitt Cancer Center. Patients underwent standard of care with different treatments as deemed appropriate by treating physician. CSF samples were obtained from lumbar punctures, surgeries, and Ommaya reservoir. CSF was evaluated for quantification of CSF circulating tumor cells (CTCs) with the Veridex CellSearch® System (VCS). RESULTS: Forty-eight patients were identified with melanoma as primary tumor, ages 29-80. Twenty-seven had LMD (median age 62) with median KPS 70. N=19 (70%) were diagnosed radiographically and n=5 (19%) with CSF cytology; n=14 (54%) had positive cytology on first LP. From 24 patients with LMD who underwent VCS, n=22 (92% patients had positive CSF CTCs. Number of CTCs/mL CSF was significantly higher in patients with LMD versus in patients without LMD (mean SD 227.6 vs. 0.07, p < 0.001). VCS sensitivity and specificity was analyzed. AUC was 0.515, with TPR 0.250 and FPR 0.286. CSF analysis and treatments were described. The median survival of those with LMD was 2.7 months. CONCLUSION: These results indicate the potential value of the VCS as an additional tool to the gold standard in the diagnosis of LMD in patients with high suspicion of the disease. Future directions involve doing prospective studies to further validate this method, and to better understand this patient population to enhance diagnostic tools and management of LMD.